Metabolic Vipaka - Abeyaratne, Dayakshi D. K.; Priya, Gagan; Kalra, Sanjay; Aye, Than Than; Aung, Moe Wint; Sumanatilleke, Manilka (Journal of Social Health and Diabetes, 2019)
Diabetes management should focus on biopsychosocial aspects and comprehensive care. The philosophical tenets of Buddhism can be a source of inspiration for both the individual with diabetes and health care provider. Buddhism preaches the immutable relationship between action and outcomes. This has a corollary in diabetes care; optimized metabolic control in diabetes is associated with improved short- and long-term outcomes and a legacy effect. Buddhism emphasizes on maintaining a “middle path.” When applied to diabetes care, this would mean avoiding both extremes of hyperglycemia and hypoglycemia and optimization of metabolic health while minimizing treatment-emergent adverse events. Mindfulness meditation-based stress reduction strategies may further improve not only psychological health but also biophysical outcomes in diabetes and merit further research.
Keywords: biopsychosocial diabetes management; metabolic karma; metabolic vipaka; mindfulness meditation